Uninterruptible power supplies and standby power systems - King Alexander (MC Graw Hill, 2003)
An engineering tutorial designed to teach basic UPS (Uninterruptible Power Supplies) design and operation. Covers rotary UPS systems and battery selection. Find complete, up to date guidance on design, installation, operation, and maintenance